Analisis Kelengkapan Pengisian Soap Pada Rekam Medis Elektronik Rawat Jalan Di Rumah Sakit Pertamina Cirebon - Herawati, Tuti (MEJORA Medical Journal Awatara, 2024)
Completeness of the health history form is important because it provides information for further treatment or action. Progress notes can use SOAP (Subjective, Objective, Analysis and Planning. The aim of this research is to determine the analysis of the completeness of SOAP filling in outpatient EMR at Pertamina Cirebon Hospital. This type of research uses descriptive methods with a quantitative approach. In this research, the data tool used is using a checklist sheet. The data collection method uses observation. The sample used for random sampling was 99 SOAP Electronic Medical Records. Based on observations of the completeness of filling out the SOAP at the Pertamina Cirebon Hospital, filling in the EMR SOAP is in the incomplete category and is still not in accordance with the Hospital's SPM which states that the completeness of filling in electronic medical records must be 100%. Results: 37 outpatient electronic medical record SOAPs with a percentage (37.4%) in the complete category and 62 outpatient EMR SOAPs with a percentage (62.6%) incomplete. It is hoped that the hospital will provide outreach to PPA about the importance of completing electronic medical records and developing an EMR application that has a 100% accuracy level in filling in completeness